Oritavancin - Karaoui, Lamis R. (2013)
Purpose The pharmacology, unique pharmacokinetic–pharmacodynamic profile, and potential future role of oritavancin in combating multidrug-resistant infections are reviewed, with an emphasis on efficacy data from Phase II and III clinical trials. Summary Oritavancin has been shown to have potent in vitro activity against vancomycin-resistant enterococci (VRE) and staphylococci, methicillin-resistant Staphylococcus aureus (MRSA), and gram-positive anaerobic bacteria. Oritavancin exhibits excellent tissue penetration and concentrates well in macrophages; its prolonged plasma half-life (195.4 hours) and extended in vitro postantibiotic effect (2.4– 7.7 hours for MRSA and 1.9–4.3 hours for VRE) might allow once-daily or alternate-day dosing. Oritavancin has been shown to have synergistic activity with several antibiotics (e.g., ampicillin, gentamicin, linezolid) against certain infections. In two Phase III clinical trials involving a total of about 1800 patients with complicated skin and skin structure infections (cSSSIs), i.v. oritavancin therapy was shown to have bactericidal activity and a safety profile comparable to those of i.v. vancomycin (plus optional oral cephalexin stepdown therapy) while requiring a significantly shorter duration of therapy; however, the compiled evidence was considered insufficient to justify marketing approval by the Food and Drug Administration, which requested additional safety and efficacy data. Two ongoing Phase III trials evaluating oritavancin for the treatment of acute bacterial SSSIs are expected to be completed in early 2013. During the clinical trials to date, the most commonly reported adverse effects among oritavancin users were headache, nausea, constipation, and phlebitis. Conclusion Oritavancin is an investigational semisynthetic antibiotic classified as a second-generation lipoglycopeptide, with promising activity against multidrug-resistant gram-positive pathogens.